Cardiac troponin elevation and mortality in takotsubo syndrome: new insights from the International Takotsubo (InterTAK) registry. (3rd October 2022) - Stahli, B E; Schindler, M; Cammann, V L; Szawan, K A; Schweiger, V; Niederseer, D; Schonberger, A; Schonberger, M; Koleva, I; Mercier, J C; Petkova, V; Wurdinger, M; et al.
Abstract: Background/Introduction: Cardiac biomarker elevations are frequently observed in Takotsubo syndrome (TTS). The clinical relevance of cardiac troponin (cTn) elevations in TTS patients remains uncertain and threshold values indicating clinically relevant myocardial injury are unknown. Purpose: This study sought to investigate the role of cTn elevations in mortality prediction of patients with TTS. Methods: A total of 2, 938 patients enrolled in the prospective International Takotsubo (InterTAK) Registry from January 2011 to February 2020 and with available data on baseline and peak cTn levels were included in the analysis. The threshold at which myocardial injury drives mortality was identified using restricted cubic spline analysis. Results: Out of 2, 938 patients, 222 (7.6%) patients died during 1-year follow-up. A more than 28.8-fold increase of cTn above the upper reference limit was identified as threshold for clinically relevant myocardial injury. Mortality at 1 year was significantly higher in patients with clinically relevant myocardial injury than in those without (Log Rank p<0.001, Figure 1). The presence of clinically relevant myocardial injury was significantly associated with an increased risk of mortality at 5 years (adjusted HR 1.58, 95% CI 1.18–2.12, p=0.002). Clinically relevant myocardial injury was related to 5-year mortality in patients with apical TTS (adjusted HR 1.57, 95% CI 1.21–2.03, p=0.001), with presence of physical stressors (adjusted HR 1.60, 95% CI 1.22–2.11, p=0.001), and with absence of emotional stressors (adjusted HR 1.49, 95% CI, 1.17–1.89, p=0.001). Conclusions: This study for the first time determined a troponin threshold for the identification of TTS patients at excess risk of mortality. These findings advance risk stratification in TTS and assist in identifying patients in need for close monitoring and follow-up. Funding Acknowledgement: Type of funding sources: Foundation.